Status of Women Employees and Job Satisfaction of Women Working in Corporate Sector - Kaang , Sugandha Kohli (Gyan Management Journal, 2024)
The present paper examines the level of job satisfaction working in the  corporate sector in the region of Gurgaon and Chandigarh. The major  findings of the study are that women are entering the corporate sector in  high numbers however their proportion is still less vis a vis their male  counterparts. In the present study, majority of the women were found  to be dissatisfied with their present jobs. There were many reasons for  dissatisfaction among the respondents. Out of which mainly were heavy  work load, long working hours, biased promotion policies and unequal  pay. Further, it was observed that unseen barriers are quite prevalent  in the corporate world due to which women are not able to reach at  the top managerial positions. These barriers are prevalent due to the  misconceptions created in respect of the ability and potential of women  employees. This patriarchal mindset of the people working in corporate  sector is the major hindrance in their growth and progress.
Keywords: Index ofjob Satisfaction; promotion policies; women employees